Test Case Selection and Prioritization for Regression Testing using Fault Severity - Sharma, Uma; Rastogi, Vedant (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Regression testing is a significant but a very expensive testing process .Test case prioritization is a technique to schedule and execute the test cases in such an order that results in increasing their ability to meet some performance goal. One of the main goal is to increase the rate of fault detection –i.e. to detect the faults as early as possible during the testing process. Test case prioritization is used to minimize the expenses of regression testing. This paper proposes a technique to select and prioritize the test cases and results in improving the rate of fault detection.